Keeping company - Kearney, Amanda, author.
1 online resource
Keywords: "This book offers up a study of relational modalities in a moment of increasingly vexed identity politics. It takes inspiration from the art of keeping company, a relational habit derived on a kincentric ontology and praxis of interconnected life among the Yanyuwa, Indigenous owners of lands and waters in northern Australia. Diving deep into this multidimensional art of relating the book critically engages with the counter habit of reductive identity politics and the flattening qualities that come with exceptionalism, individuated rights, limited empathic reach and a lack of enchantment in the other. Moving between ethnographic insights, conceptual analysis, and personal reflection Keeping Company offers an accessible engagement with some of the tricky aspects of identity politics as navigated in the present moment across sites of cultural difference. It will interest scholars and students from anthropology, sociology, philosophy and Indigenous studies, and others who are driven to be in better relationship with the world, with their neighbours, with strangers and with themselves"--